The ASEAN Way and Regional Environmental Cooperation: Explaining Forest Climate Policies in Southeast Asia - Latifah Ratu Dea; Wawan Budi Darmawan; Deasy Silvya Sari (GoAcademica Research & Publishing, 2026)
Climate change and accelerating deforestation have intensified the need for regional cooperation to address forest-related environmental challenges in Southeast Asia. As one of the world's most forest-rich regions, Southeast Asia has witnessed the development of various regional initiatives and policy frameworks that seek to strengthen cooperation on forest conservation and climate change mitigation. Limited attention has been given to the role of the ASEAN Way as a normative foundation that shapes the development of regional forest climate policies. This study aims to explain how the principles of the ASEAN Way influence regional environmental cooperation in the formulation of forest climate policies in Southeast Asia. Employing a qualitative research design, the study uses document analysis of ASEAN declarations, regional agreements, strategic plans, policy frameworks, and relevant academic literature. The ASEAN Way guides the analysis as an informal regional institution characterized by consensus, consultation, non-interference, respect for sovereignty, and informality. The findings suggest that these principles have significantly influenced the development of regional environmental cooperation by promoting consensus-based decision-making, voluntary commitments, and flexible institutional arrangements in the formulation of forest climate policies. This article contributes to the International Relations literature by demonstrating how regional norms shape environmental cooperation and influence regional policy development, thereby providing a normative and institutional explanation for the emergence and characteristics of forest climate policies in Southeast Asia.